Costa Rica’s Marine Protected Areas: status and perspectives - Alvarado Barrientos, Juan José (2012)
With 51 100km2 of terrestrial area and 589 000km2 of national waters, Costa Rica is considered one of the countries with the greatest biodiversity. It has approximately 3.5% of the world marine species. In the last four decades, Costa Rica has done a considerable effort to create a representative system of Protected Areas (PA), mainly terrestrial. We present an assessment of the current situation of the Marine Protected Areas (MPA) in Costa Rica, through an historical analysis, and an evaluation of their distribution, coverage and management categories. Costa Rica has 166 protected areas covering 50% of the coastline; of these 20 are MPAs, classified as National Parks (90.6%), National Wildlife Refuges (6.6%), Wetlands (1.5%), Biological Reserves (1%), and one Absolute Natural Reserve (0.3%). According to IUCN criteria, 93.7% correspond to category II, 5% to IV and 1.3% to I. The marine protected surface is 5 296.5km2, corresponding to 17.5% of the territorial waters and 0.9% of the Exclusive Economic Zone. The median distance between MPAs is 22.4km in the Pacific and 32.9km along the Caribbean. The median size is close to 54km2. The main threats to MPAs are the lack of coordination between governmental agencies, limited economic resources, restricted patrolling and control, poor watershed management, and rampant coastal alteration.